Strategi Penanganan Orang Terlantar Miskin Sebagai Upaya Pemenuhan Hak Kesejahteraan Sosial Oleh Dinas Sosial Kota Surakarta - Cornelius Brilian Boni Nugraha; Triana Rejekiningsih (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
The problem of poverty and neglect in Indonesia is still a major challenge, especially in big cities like Surakarta. The Surakarta City Social Service has the responsibility to handle the problems of neglected people so that they get proper social welfare rights. This study aims to analyze the strategies for handling neglected people implemented by the Surakarta City Social Service, especially in the Social Rehabilitation Sub-Division. The method used in this study is a qualitative method with a descriptive approach. Data were obtained through interviews with Social Service employees and observations of the social rehabilitation services provided. The results of the study showed that the strategies used included data collection, provision of shelters, provision of health and social services, and reintegration into society. Although this strategy is quite effective, there are several obstacles such as budget constraints and lack of public awareness. Therefore, synergy is needed between the government